Cytokines and Inflammatory Mediators 2018
DOI: 10.1136/annrheumdis-2018-eular.4463
|View full text |Cite
|
Sign up to set email alerts
|

AB0057 Decreased irisin level as risk factor of pathological fractures in rheumatoid arthritis patients

Abstract: BackgroundRecent studies have been suggested that adipokines and myokines may be implicated in bone metabolism and pathogenesis of osteoporosis (OP).1 Previous studies have revealed inverse correlation between irisin levels and vertebral fragility fractures, but no significant correlation was found between irisin and bone mineral density (BMD) as well as with lean weight. There is no previously published data about irisin levels in rheumatoid arthritis (RA) patients.2–4 ObjectivesTo investigate serum irisin le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
3
6
0
Order By: Relevance
“…[9,8] There are some studies that identify low irisin levels in RA compared with controls. [17,26] Our results are concordant with these studies showing lower serum levels of irisin in RA group with respect to our group of women without rheumatic disease.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…[9,8] There are some studies that identify low irisin levels in RA compared with controls. [17,26] Our results are concordant with these studies showing lower serum levels of irisin in RA group with respect to our group of women without rheumatic disease.…”
Section: Discussionsupporting
confidence: 92%
“…Lavrova et al observed in their RA patients that low irisin concentrations were related with osteoporotic fractures in general. [17] In the best of our knowledge this study is the first to assess the relation between irisin levels and osteoporotic VFs in RA patients. We identified that low irisin concentrations increased the risk of osteoporotic VFs in RA patients.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In such study, the authors found that patients with more severe disease symptoms exhibited lower serum levels of irisin, which is in accordance with our results (45). Also in this line, previous studies performed in other rheumatic diseases reported an inverse association between irisin serum levels and disease activity (22,(46)(47)(48). In addition, patients treated with conventional DMARDs and NSAIDs exhibited lower serum irisin levels.…”
Section: Discussionsupporting
confidence: 92%